INTEGRATING NURSING CONTEXT AND TECHNOLOGY USAGE FOR ENGLISH SPEAKING EMPOWERMENT - YOHANES HERI PRANOTO (Sriwijaya University Learning and Education International Conference, 2016)
English for specific purposes (ESP) must be taught to meet particular needs of non-English language students (Hutchinson & Waters, 1987, p.21). It gives direct suggestion that learning process should be designed in such away not only to meet the learning objectives of the students but also to give the students meaningful and enjoyable learning experiences (Crawford, 2013, p.181). The condition becomes more challenging when the ESP teachers are only having English language background. It implies that learning context, which meets the students’ needs, should be carried out in learning process along with the suitable and enjoyable learning strategies where the students can feel the pleasure instead of pressure. By considering the three steps of ESP course designing suggested by Nitu (2002, p.154), this paper aims at proving the effectiveness of integrating the students’ learning contexts and the students’ pleasure to empower the students’ speaking performance in Health Science Faculty of Musi Charitas Catholic University Palembang. This study belongs to experimental research with pre- and post-design. By the end of the study, it was proven that integrating the nursing field context and the usage of technology in the classroom can help the students improve their English speaking skills. For evidential information, some videos of learning process are presented.